Bibliometric Insights into Women Entrepreneurship : A Global Perspective on Key Contributions and Challenges - Loso Judijanto; Ivon Arisanti (Westscience Press, 2024)
This study employs a comprehensive bibliometric analysis to explore the landscape of research on women's entrepreneurship using VOSviewer software. Through a series of visualizations, we examine the co-authorship networks, key thematic focuses, geographical distributions, and the temporal dynamics of the field from 2000 to 2022. Our findings reveal significant collaborative dynamics among scholars, with central figures acting as pivotal nodes in the academic network. Thematic analysis highlights